Perbandingan Sistem Pembiayaan Kesehatan Sebelum dan Selama Pelaksanaan Jaminan Kesehatan Nasional (JKN) di Kabupaten Kuningan Tahun 2014 - Suparman, Rossi; Heriana, Cecep (Sekolah Tinggi Ilmu Kesehatan Kuningan, 2015)
Background: Indonesia implementing health financing system of social insurance starting on January 1, 2014 Health financing policy in this year ensured that all Indonesian society in terms of health insurance. Kuningan Regency Society already registered BPJS approximately 52%. Kuningan district health budget allocation in 2014 reached 4.9% of regional budget. When a policy is launched it will cause a change before or when the policy is launched insluding policy National Health insurance. This study aims to describe the comparison of the health financing system before and during the implementation of the national health insurance (JKN) in the Kuningan District. Methods: This study is a descriptive study with a qualitative approach. Subject of research was stakeholders, profesional organization, college. Characteristics of data collected include primary data obtained from interviews using an interview guide, while the secondary data obtained with the document study and the data were analyzed qualitatively. Result: The funds of health financing before JKN was approved from the state budget, provincial budget and the district also levies charges. Currently plus funds from the public (non-PBI). Allocation of health financing before and after JKN has not changed still 4,9% of the budget. Before JKN was approved, health care payment was using fee for service, and currently uses pattern CBG's INA rates. Governance in the region has not changed, the law refers to national legislation for the regulation of only a capitation system. The role of stakeholders or any agency in JKN was as implementers, monitoring and evaluation. The major of management role JKN program, each agency work together in order to all citizens will have become participants BPJS in Kuningan District. Conclusion and recommendation: health financing system in Kuningan district generally has not changed due to the allocation of health funding still does not tend to rise. Expected to increase the allocation of Health funding, and poor people who are not covered can be covered BPJS.